Avenues for Professional Development: Faculty Perspectives from an Indian Medical School - Abraham, RR; Pallath, V; AM, C; Ramnarayan, K; Kamath, A (Kathmandu University Medical Journal, 2014)
Background Medical school faculty in India are challenged to balance teaching and professional development. Melaka Manipal Medical College (MMMC), Manipal Campus, Manipal University, India offers the Bachelor of Medicine and Bachelor of Surgery (MBBS) program. The institution incorporates certain effective practices based on adult learning principles which are aimed at fostering the professional development of faculty members. Objectives The present study was undertaken to explore the perceptions of faculty members regarding the scope for professional development at Melaka Manipal Medical College, Manipal Campus. Methods In September 2009, a questionnaire comprising items (23) focusing on five adult learning principles (active participation, relevant learning, constructive feedback, safe, non-threatening environment and previous experiences) was designed and faculty members (n=23) were asked to respond to it on a 5-point Likert scale. Additionally, a force field analysis was conducted by asking the faculty to identify three factors which facilitated them to consciously get involved in professional development activities. They were also asked to identify three unfavorable factors that hindered their professional development. Results Among the five characteristics, relevant learning was found to have a high mean score. Frequency analysis of responses revealed that at Melaka Manipal Medical College, there was ample scope for relevant self-learning that fosters professional development (91.3%). Force field response analysis revealed Melaka Manipal Medical College offered considerable flexibility and opportunities for continuing professional development along with faculty members’ prevailing role as teachers. Nevertheless, the need for more research facilities and funds was highlighted. Conclusions Adherence to adult learning principles may provide avenues for professional development in medical schools. An organized attempt to make the medical school faculty aware of the scope of these practices appears to be necessary to nurture professional development in settings where there are resource constraints. DOI: http://dx.doi.org/10.3126/kumj.v10i4.10997 Kathmandu Univ Med J 2012;10(4):60-65